MIRRORING THE “OTHER”: ORIENTALISM, NOMADS AND ETHNOMASQUERADING IN LAWRENCE’S SEVEN PILLARS OF WISDOM - Corrizzato, Sara; Goracci, Giada (European Scientific Journal, ESJ, 2014)
Postcolonial theory is mainly concerned with the concept of “otherness”. This term implies complexities to its definition in that it might include other concepts, such as doubleness, identity, responsibility, alter ego and enigma to and of the self. As a complex and multifarious term, Otherness conventionally evokes another pivotal aspect of the theory that is “difference”. This article381 ventures into the way in which Thomas Edward Lawrence, in his masterpiece Seven Pillars of Wisdom, sees “the Other” and, secondly, what possible reasons make him partially change his vision of/on the oriental culture. The focus will be especially set on Lawrence’s journey to Arabia as a crucial point to his personal development. Furthermore, the article will take into account Lawrence’s role in the revolt in which he took part and what kind of relationship he had both with his English superiors and with Arab soldiers. Finally, to better understand Lawrence’s interior change, it will be indispensable to analyse three important theories: Orientalism, the concept of “nomad”, and the notion of Ethnomasquerading.